Dubinin isotherms versus the Brouers–Sotolongo family isotherms: A case study - Francois Brouers; Francisco Marquez-Montesino (Adsorption Science & Technology, 2016)
We show how the Dubinin isotherm and its extensions can be related to the isotherms derived from the general Brouers–Sotolongo isotherm. We compare them using benzene vapor adsorbed on activated carbon data from one of the original Dubinin’s paper. We use the same procedure to analyze data from the thesis of Francois Marquez-Montesino on the adsorption on activated carbons prepared from Pinus caribaea saw dust. We conclude by proposing a simple methodology to determine the macroscopic information given by genuine statistical isotherms.